Judicial Disparities in Asset Confiscation Rulings in Online Trading Cases in Indonesia: A Maqashid al-Shariah Analysis - Sahnaz Kartika; Muhammad Syukri Albani Nasution; Hasan Matsum (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This study examines the disparity in court rulings concerning the status of confiscated assets in online trading crime cases. The Banten High Court Decision No. 117/Pid.Sus/2022/PT BTN ordered the return of assets to victims, whereas the Bandung High Court Decision No. 1/Pid.Sus/2023/PT BDG ruled that such assets be confiscated for the state. This divergence generates legal uncertainty and raises fundamental questions of justice. The research aims to critically assess the extent to which these rulings are consistent with the objectives of maqāṣid al-sharīʿah, particularly the principle of ḥifẓ al-māl (protection of property). A normative legal approach is employed, drawing on statutory analysis, judicial decisions, and comparative perspectives. The findings indicate that the Banten ruling more closely reflects ḥifẓ al-māl by safeguarding victims’ property rights, while the Bandung ruling risks undermining justice, as the state did not directly incur losses. Beyond highlighting this jurisprudential inconsistency, the study underscores the urgency of harmonizing regulatory frameworks so that the principle of ḥifẓ al-māl can be systematically integrated into Indonesian criminal justice practice, thereby advancing substantive justice and strengthening public trust in the law.